2012
DOI: 10.1590/s1679-87592012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Forage fauna in the diet of bigeye tuna (Thunnus obesus) in the western tropical Atlantic Ocean

Abstract: A total of 291 stomachs of bigeye tuna caught in the Western tropical Atlantic Ocean ranging between 60 and 195 cm fork length, were analyzed between October 2004 and November 2005. The vertical distribution of prey was studied in relation to their feeding strategies. A total of 83 prey items were identified of which 46 were fishes, represented mainly by brephoepipelagic, and meso-bathypelagic fishes; 20 cephalopods, 13 pelagic crustaceans, one tunicate, one heteropod and one pteropod. The Caribbean pomfret Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Furthermore, the presence of Brachyuran megalopae in the stomachs of bigeye and yellowfin tunas could be interpreted as an evidence of their skills to feed over small prey, a similar feeding habit that was observed from yellowfin (Buckley & Miller, ; Dragovich, ; Graham et al, ; Potier et al, ; Rohit et al, ), and also from bigeye (Potier et al, ; Vaske‐Jr et al, ). For example, Ménard et al () studying the prey‐predator relationship for bigeye and yellowfin tunas in the Pacific Ocean, concluded that during the growth both species continue to feed on small prey, but bigeye select larger prey than yellowfin, when available.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Furthermore, the presence of Brachyuran megalopae in the stomachs of bigeye and yellowfin tunas could be interpreted as an evidence of their skills to feed over small prey, a similar feeding habit that was observed from yellowfin (Buckley & Miller, ; Dragovich, ; Graham et al, ; Potier et al, ; Rohit et al, ), and also from bigeye (Potier et al, ; Vaske‐Jr et al, ). For example, Ménard et al () studying the prey‐predator relationship for bigeye and yellowfin tunas in the Pacific Ocean, concluded that during the growth both species continue to feed on small prey, but bigeye select larger prey than yellowfin, when available.…”
Section: Discussionmentioning
confidence: 83%
“…Such results are very close to that presented by Vaske‐Jr et al () and Ruderhausen et al () from yellowfin tuna caught in the western Atlantic. However, Vaske‐Jr et al () found a higher number of prey items from bigeye tuna caught by longliners in southwestern Atlantic, possibly because they had a broader size range and were caught in a wider area.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diets of its congeners have been investigated more frequently; for example, Brama caribbea Mead 1872 and Brama japonica Hilgendorf 1878 consumed euphausiids, amphipods, squid and fishes (Wada & Honda, 1992;Savinykh, 1994;Watanabe et al ., 2003Watanabe et al ., , 2006Vaske et al ., 2008). In turn, pomfrets are important food for tunas and billfishes (Vaske et al ., 2004(Vaske et al ., , 2012.…”
Section: Introductionmentioning
confidence: 99%